Implementasi Aplikasi Polri Super App Presisi Untuk Pelayanan Surat Keterangan Catatan Kepolisian (Skck) Di Polres Solok Selatan - Efendi, Irwen; Syafril, Rizki (Jurnal Teori dan Riset Administrasi Publik, 2025)
This study aims to analyze the implementation of the Polri Super App Presisi application in the service process of issuing Police Record Certificates (SKCK) in the jurisdiction of Polres Solok Selatan. The background of this research is based on ongoing complaints from the public regarding the less than optimal effectiveness of the application’s implementation in the online SKCK issuance process introduced by the Indonesian National Police. This study uses a qualitative approach, with data collection techniques through interviews, observations, and documentation. Informants were selected using purposive sampling, totaling 10 people. Data were analyzed using Sugiyono’s method through the stages of data reduction, data presentation, and conclusion drawing. The research results indicate that the implementation of the Polri Super App has been carried out appropriately and effectively. Additionally, the application provides significant benefits to the community of Solok Selatan Regency. In the program’s implementation, socialization of the Polri Super App was also conducted across various layers of society.